NPM : optimization of purchasing process - Martinovová, Nikola; Pilař, Tomáš, 1985-; Dvořák, Jiří; Vysoká škola ekonomická v Praze. Fakulta managementu (2014)
The theoretical part will be focused on presenting information within the process management. Some of the pieces of this theoretical information will be were slightly modified by internal Continental procedures and applied in the practical part of the thesis in order to redesign current purchasing process of non production material. The contents of the practical part of this thesis are the analysis of the current purchasing process of non-production material in the plant of Continental. The intention is to identify the waste and obstacles in the process. The main target is to improve the process in consideration of efficiency, lead time reduction and, if applicable, cost savings. Once the waste in the process is identified, the 100% value added ideal state is going to be developed, under consideration of implementing the improvements, which have been identified in the current state. Based on the differences between the current state and the ideal state of the process, the future state is going to be mapped.
Vedoucí práce: Tomáš Pilař
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2015
Obsahuje bibliografii
Rok obhajoby 2015
Keywords: procesní management; optimalizace; nákup; management nákupu; management [obor dipl. práce]; diplomové práce; process management; optimization; purchasing; purchasing management; master's theses